If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(3x + 9) = 2x + 3 Reorder the terms: 8x + -1(9 + 3x) = 2x + 3 8x + (9 * -1 + 3x * -1) = 2x + 3 8x + (-9 + -3x) = 2x + 3 Reorder the terms: -9 + 8x + -3x = 2x + 3 Combine like terms: 8x + -3x = 5x -9 + 5x = 2x + 3 Reorder the terms: -9 + 5x = 3 + 2x Solving -9 + 5x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -9 + 5x + -2x = 3 + 2x + -2x Combine like terms: 5x + -2x = 3x -9 + 3x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + 3x = 3 + 0 -9 + 3x = 3 Add '9' to each side of the equation. -9 + 9 + 3x = 3 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 3 + 9 3x = 3 + 9 Combine like terms: 3 + 9 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 3x(5-n)=27 | | 15x^2+28x+5=0 | | 9a^2-18ab+8b^2=0 | | -12-6x=6x-12 | | 45t-21-6t^2=0 | | 3s(10s+7)=0 | | 5-8x-4x^2=0 | | 3x^2-22x+35=0 | | 5-4x-12x^2=0 | | -(5y+2)-(-4y-3)=1 | | 8x^5+10x^4+3x^3=0 | | 5x/8=-3x/8+1 | | n-38=-27 | | 6(z+9)+4z=8-(z+2) | | 3(x-1)=3+2(x-3) | | (0.75d^2)-0.9*d-1.5=0 | | x^2+x-82=0 | | 5p+6=8+4p | | -7(-3)-[8-(3-5)]=11 | | 15x^2-25x-10=0 | | -7(-3)-[8-93-5]=11 | | 3x-150=525 | | 9y+6y^2-15=0 | | 28-10v-2v^2=0 | | 2x^2-3xy+4y^2+6x-3y-4=0 | | 25-20v+4v^2=0 | | 5x+14=619 | | -(-7x+6y+9)= | | 9b^2+27b+20=0 | | -8y-11=y+7 | | y^2+11y-22=0 | | 9b^2+27b+2=0 |